LEMPU' AS A PILLAR OF CHARACTER EDUCATION: AN EFFORT TO PRESERVE THE LOCAL WISDOM OF THE BUGIS TRIBE IN SCHOOLS - Ilyas, Nurmukhsin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The preservation of local wisdom values is crucial in shaping the nation's character, one of which is the value of Lempu' from Bugis culture, which emphasizes the importance of honesty and integrity. This paper explores the role of Lempu' value in character education in schools as an effort to preserve local culture and build students' character. This research uses a qualitative method with a literature review approach to analyze the implementation of Lempu' values in the curriculum and educational practices. The study results show that the integration of local cultural values, such as Lempu', can improve students' moral quality, strengthen social relations, and form honest and responsible individuals. Teachers act as role models in teaching this value, while its implementation in the curriculum and school activities can create an educational environment that supports students' holistic character development. The implementation of the Lempu' value not only strengthens students' character, but also becomes a strategic step in preserving Bugis culture in the midst of globalization. Keywords: Bugis Culture, Local Cultural Wisdom, Lempu', Character Education